Toner containing conductive particles and preparation method thereof

By using the molybdenum disulfide composite particles and graphyne particles coated with conductive polymers in the toner, the problems of increasing powder consumption, decreasing transfer rate and decreasing color density during the mixed use of different toners are solved, and the effects of reducing powder consumption, increasing transfer rate and maintaining color density stability are achieved.

CN119668060APending Publication Date: 2025-03-21邯郸汉光办公自动化耗材有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510145270.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-10
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

In the compatible market, when toners from different manufacturers are mixed, it is easy to cause problems such as increasing powder consumption, decreasing transfer rate and decreasing color density. The reason is that the raw materials of different toners vary greatly, resulting in an increase in electrically reverse powder and a wide charge distribution.

Method used

Toner containing conductive particles is used. The toner masterbatch contains binder resin and graphite alkyne particles. The external additive is a composite molybdenum disulfide disulfide coated with conductive polymer. The combination of these components reduces the problem of the anti-electric substance caused by the differences in different materials.

Benefits of technology

The amount of powder added in the non-developing area is reduced, the phenomenon of flying powder is reduced, the amount of powder consumed is reduced, the transfer rate is improved, and the color density of the image is maintained is stable, the charge accumulation of toner is suppressed, and the charging stability of the developer is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005266256240000111
    Figure BDA0005266256240000111
  • Figure BDA0005266256240000122
    Figure BDA0005266256240000122
  • Figure BDA0005266256240000123
    Figure BDA0005266256240000123
Patent Text Reader

Abstract

The invention relates to a toner containing conductive particles and a preparation method thereof, and belongs to the technical field of development consumables of electrophotographic equipment. Comprising a toner master batch and an external additive, wherein the toner masterbatch includes a binder resin and graphdiyne particles; the external additive comprises molybdenum disulfide composite particles coated with a conductive polymer; the external additive is attached to the surface of the toner masterbatch. The toner master batch contains graphdiyne particles, meanwhile, the molybdenum disulfide composite particles coated with the conductive polymer serve as an external additive, and the graphdiyne particles and the molybdenum disulfide composite particles are matched for use, so that the problem that counter-electricity substances exist due to differential friction of different materials is solved, the powder feeding amount of a non-developing area is reduced, the powder flying phenomenon is reduced, the powder consumption amount is reduced, and the transfer printing rate is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a toner containing conductive particles and a preparation method thereof, belonging to the technical field of developing consumables for electronic photographic equipment. Background Art

[0002] In the compatible market, mixing toners from different manufacturers in the same series sometimes causes problems such as increased powder consumption, decreased transfer rate, and decreased color density. The reason is that the raw materials of different toners are very different, and the reverse charge powder increases during the development process, resulting in a wide charge distribution. In the image formation of electronic photography, for example, using a magnetic single-component developer, i.e., toner, it is necessary to have excellent color density stability (the ability to continuously and stably form an image of the required color density) and good charge stability and durability. In addition, low powder consumption and high transfer rate can further enhance the competitiveness of the product quality. Therefore, it is necessary to produce a toner with excellent competitiveness, color density stability, and charge stability. Summary of the invention

[0003] In view of the above, an object of the present invention is to provide a toner containing conductive particles and a method for preparing the same.

[0004] To achieve the above objectives, the technical solution of the present invention is as follows.

[0005] A toner containing conductive particles, comprising a toner master particle and an external additive; wherein the toner master particle comprises a binding resin and graphyne particles; the external additive comprises a molybdenum disulfide composite particle coated with a conductive polymer; and the external additive is attached to the surface of the toner master particle;

[0006] The mass fraction of the binding resin in the toner masterbatch is 40% to 95%, the mass of the graphyne particles is 0.05% to 10% of the binding resin, and the mass of the molybdenum disulfide composite particles coated with the conductive polymer is 0.05% to 2% of the toner masterbatch.

[0007] Preferably, the mass fraction of the binding resin in the toner masterbatch is 55% to 90%, the mass of the graphyne particles is 1% to 5% of the mass of the binding resin; and the mass of the molybdenum disulfide composite particles coated with the conductive polymer is 0.1% to 1% of the mass of the toner masterbatch.

[0008] Preferably, the Graphene Oxide Particles have a sheet diameter of 2 to 10 μm, a thickness of 5 to 13 nm, and an electrical conductivity of (0.5 to 4)×10 2 S / m.

[0009] Preferably, in the molybdenum disulfide composite particles coated with the conductive polymer, the coverage of the conductive polymer on the molybdenum disulfide particles is 20% to 70%, the coating thickness is 0.1 to 10 nm, the particle size of the composite particles is 50 to 500 nm, the resistivity is below 40 Ω·cm, and the sphericity coefficient is greater than 0.95. More preferably, in the molybdenum disulfide composite particles coated with the conductive polymer, the coverage of the conductive polymer on the molybdenum disulfide particles is 30% to 50%, the particle size of the composite particles is 100 to 200 nm, the resistivity is below 10 Ω·cm, and the moisture content is less than 0.5%.

[0010] Preferably, in the molybdenum disulfide composite particles coated with a conductive polymer, the conductive polymer is one or more of polypyrrole and its derivatives, polyaniline and its derivatives, polythiophene and its derivatives.

[0011] Preferably, the toner masterbatch further comprises a colorant, a charge regulator and a release agent.

[0012] Preferably, the external additives further include silicon dioxide and metal oxide particles.

[0013] Preferably, the binder resin contains 85% or more of thermoplastic resin by mass.

[0014] Preferably, the colorant is carbon black or magnetic iron oxide black, the mass of the carbon black is 10% to 15% of the mass of the binding resin, the mass of the magnetic iron oxide black is 60% to 150% of the mass of the binding resin; the mass of the charge regulator is 2% to 10% of the mass of the binding resin, and the mass of the release agent is 2% to 20% of the mass of the binding resin.

[0015] A method for preparing a toner containing conductive particles according to the present invention comprises the following steps:

[0016] First, the components of the toner masterbatch are mixed, extruded through an extruder, cooled, crushed, and sieved to obtain the toner masterbatch; then, external additives are added, mixed, and sieved to obtain a toner containing conductive particles.

[0017] Beneficial Effects

[0018] The present invention provides a toner containing conductive particles, wherein the toner masterbatch contains graphyne particles, and molybdenum disulfide composite particles coated with conductive polymers are used as external additives. The two are used in combination to reduce the problem of the existence of counter-electric substances caused by the friction between different materials, thereby reducing the amount of powder on the non-developing area, reducing the flying powder phenomenon, reducing the powder consumption, and improving the transfer rate. In addition, reducing the accumulation of the toner charge can inhibit the potential difference between the developer carrier and the toner charging component and the toner from becoming too large, causing toner stratification, making the newly added toner on the developer carrier low in charge and the charge distribution wide, causing the problem of color density reduction. The toner of the present invention reduces the powder consumption and improves the transfer rate when the toner is added with powder twice and continuously printed, and the color density of the formed image does not decrease significantly and can also remain stable. The toner of the present invention can make the charge more concentrated in the developing device.

[0019] In the present invention, the molybdenum disulfide composite particles coated with a conductive polymer are used as external additives to make the graphyne particles uniformly dispersed on the surface of the toner masterbatch. If the composite particles are used alone, the particle size of the composite particles is too small to meet the requirements. DETAILED DESCRIPTION

[0020] The present invention will be further described in detail below in conjunction with specific embodiments.

[0021] A colorant containing conductive particles comprises a colorant master particle and an external additive; wherein the colorant master particle comprises a binding resin and graphyne particles; the external additive comprises molybdenum disulfide composite particles coated with a conductive polymer; and the external additive is attached to the surface of the colorant master particle.

[0022] In some embodiments, the mass fraction of the binder resin in the colorant masterbatch is 40% to 95%, the mass of the graphyne particles is 0.05% to 10% of the mass of the binder resin, and the mass of the molybdenum disulfide composite particles coated with the conductive polymer is 0.05% to 2% of the mass of the colorant masterbatch; more preferably, the mass fraction of the binder resin in the colorant masterbatch is 55% to 90%, the mass of the graphyne particles is 1% to 5% of the mass of the binder resin; the mass of the molybdenum disulfide composite particles coated with the conductive polymer is 0.1% to 1% of the mass of the colorant masterbatch.

[0023] In some embodiments, the Graphene particles have a sheet diameter of 2 to 10 μm, a thickness of 5 to 13 nm, and a conductivity of (0.5 to 4)×10 2 S / m.

[0024] In some embodiments, in the molybdenum disulfide composite particles coated with the conductive polymer, the coverage of the conductive polymer on the molybdenum disulfide particles is 20% to 70%, the coating thickness is 0.1 to 10 nm, the particle size of the composite particles is 50 to 500 nm, the resistivity is below 40 Ω·cm, and the sphericity coefficient is greater than 0.95. More preferably, in the molybdenum disulfide composite particles coated with the conductive polymer, the coverage of the conductive polymer on the molybdenum disulfide particles is 30% to 50%, the particle size of the composite particles is 100 to 200 nm, the resistivity is below 10 Ω·cm, and the moisture content is less than 0.5%.

[0025] In some embodiments, in the conductive polymer-coated molybdenum disulfide composite particles, the conductive polymer is one or more of polypyrrole and its derivatives, polyaniline and its derivatives, polythiophene and its derivatives.

[0026] In some embodiments, the toner masterbatch further includes a colorant (such as a black colorant, a color colorant; the black colorant may also be a colorant toned to black using a yellow colorant, a magenta colorant, and a cyan colorant; the color colorant includes, for example, a yellow colorant, a magenta colorant, and a cyan colorant), a charge regulator (negatively charged agents may be organic metal coordination compounds and chelate compounds, for example, monoazo metal coordination compounds, acetylacetone metal coordination compounds, and metal coordination compounds of aromatic hydroxycarboxylic acids and aromatic dicarboxylic acids. Positively charged agents include azine compounds, direct dyes, acid dyes, alkoxyamines, alkylamides, quaternary ammonium salts, and resins containing quaternary ammonium cation groups. The charge control agent is preferably a quaternary ammonium salt or a resin containing a quaternary ammonium cation group) and a release agent (such as aliphatic hydrocarbon waxes, oxygenated forms of aliphatic hydrocarbon waxes, Examples of the present invention include ester waxes, plant waxes, animal waxes, mineral waxes, ester waxes with fatty acid esters as the main component, and waxes obtained by partially or completely deoxidizing fatty acid esters. Examples of aliphatic hydrocarbon waxes include low molecular weight polyethylene, low molecular weight polypropylene, polyolefin copolymers, polyolefin waxes, microcrystalline waxes, paraffin waxes, and Fischer-Tropsch waxes. Examples of the oxides of aliphatic hydrocarbon waxes include oxidized polyethylene waxes and block copolymers of oxidized polyethylene waxes. Examples of plant waxes include candelilla wax, carnauba wax, Japan wax, simmondsia chinensis wax, and rice bran wax. Examples of animal waxes include beeswax, lanolin wax, and spermaceti. Examples of mineral waxes include ozokerite, ceresin, and petrolatum. Examples of ester waxes with fatty acid esters as the main component include montanic acid ester waxes and castor wax. Examples of waxes obtained by partially or completely deoxidizing fatty acid esters include deoxidized carnauba wax. The release agent is preferably carnauba wax).

[0027] In some embodiments, the external additive further includes silicon dioxide, metal oxide particles (such as aluminum oxide, zinc oxide, titanium dioxide).

[0028] In some embodiments, the binder resin contains a thermoplastic resin, and more preferably contains a thermoplastic resin in a proportion of 85% by mass or more of the total binder resin. Examples of thermoplastic resins include styrene resins, acrylic resins, olefin resins (more specifically, polyethylene resins, polypropylene resins, etc.), vinyl resins (more specifically, vinyl chloride resins, polyvinyl alcohol, vinyl ether resins, N-vinyl resins, etc.), polyester resins, polyamide resins, and polyurethane resins. In addition, copolymers of the above-mentioned various resins, i.e., copolymers into which optional repeating units are introduced into the above-mentioned resins (more specifically, styrene-acrylic resins, styrene-butadiene resins, etc.) can also be used as binder resins. The binder resin is preferably a polyester resin.

[0029] In some embodiments, the colorant includes carbon black or magnetic iron oxide black, the mass of the carbon black is 10% to 15% of the mass of the binding resin, and the mass of the magnetic iron oxide black is 60% to 150% of the mass of the binding resin; the mass of the charge regulator is 2% to 10% of the mass of the binding resin, and the mass of the release agent is 2% to 20% of the mass of the binding resin.

[0030] A method for preparing a toner containing conductive particles according to the present invention comprises the following steps:

[0031] First, the components of the toner masterbatch are mixed, extruded through an extruder, cooled, crushed, and sieved to obtain the toner masterbatch; then, external additives are added, mixed, and sieved to obtain a toner containing conductive particles.

[0032] In the following examples or comparative examples:

[0033] The conductive polymer-coated molybdenum disulfide composite particles are prepared by the following method, which comprises the following steps:

[0034] (1) Adding a single layer or multiple layers of molybdenum disulfide powder ≤ 2 μm, sodium carbonate or sodium bicarbonate to an aqueous solvent or an organic solvent to obtain a mixed solution A, wherein the initial concentration of molybdenum disulfide in the mixed solution is 2 to 200 mg mL -1 The initial concentration of sodium carbonate or sodium bicarbonate is 5-40 mg mL -1 ;

[0035] (2) subjecting the mixed solution A to ultrasonic stripping treatment at a power of 180 to 200 W for 1 to 3 hours;

[0036] (3) After ultrasonic stripping, the mixture is centrifuged at 2000-3000 rpm for 20-30 min to remove the unstripped molybdenum disulfide powder. The suspension is collected to obtain a suspension containing 50-200 nanometer-sized modified molybdenum disulfide. The concentration of the dispersion is 2-100 mg mL -1 ;

[0037] (4) The conductive polymer monomer is modified and protonated with concentrated sulfuric acid at a ratio of 1:1 to 1:4. The modified conductive polymer monomer and the molybdenum disulfide dispersion are mixed at a ratio of 1:2 to 1:10 to obtain a mixed dispersion, and then an initiator is added to the mixed dispersion to polymerize the conductive polymer monomer in the mixed dispersion in situ to obtain a molybdenum disulfide / conductive polymer composite particle mixed solution, and the composite particles are obtained by high-speed centrifugation at 6500r. Composite particles with a particle size of 50nm to 500nm are obtained. The polymerization temperature is 0 to 5 degrees Celsius, and the polymerization time is 10 to 24 hours. The initiator is iron toluenesulfonate, iron p-toluenesulfonate, ammonium ferrous sulfate, ammonium thiosulfate, ferric chloride or ammonium persulfate, and the addition ratio is a mass ratio of the activated conductive polymer monomer of 1:1 to 1:10.

[0038] Example 1

[0039] 50 parts of Sanyo Chemical CMO500 binder resin, 50 parts of Sanyo Chemical CMO330 binder resin, 80 parts of Bayer E8706 magnetic powder, 5 parts of Sasol Fischer-Tropsch wax 9535, 2 parts of Dinglong P12 charging agent, 1 part of graphyne particles (with a diameter of 4 μm, a thickness of 9 nm, and a conductivity of 1.5×10 2 S / m,), mixed in a Henschel high-speed mixer; then the mixed material was extruded through a twin-screw extruder, the extruded material was cooled, crushed, and classified to obtain a toner masterbatch with a median particle size of 8.0 μm.

[0040] Silica with a diameter of 12-50 nm (Cabot TG-7120, added in an amount of 1 g TG-7120 per 100 g masterbatch) treated with aminosilane and hexamethyldisilazane, polythiophene-coated molybdenum disulfide composite particles (the coverage of the conductive polymer on the molybdenum disulfide particles is 50%, the coating thickness is 4 nm, the particle size of the composite particles is 100 nm, the resistivity is 10 Ω·cm, and the sphericity coefficient is greater than 0.95; the addition amount is 0.5 g per 100 g masterbatch), and alumina particles (AKP3000, added in an amount of 0.5 g per 100 g masterbatch) are added to the toner masterbatch in sequence and uniformly mixed, and then put into a Henschel mixer for mixing. Finally, the mixed materials are screened through a 150-mesh vibrating screen to obtain a toner containing conductive particles.

[0041] Example 2

[0042] In this embodiment, the addition amount of graphyne particles is 0.05 parts, and the rest is the same as in Embodiment 1.

[0043] Example 3

[0044] In this embodiment, the amount of Graphene Olefin Particles added is 2 parts, and the rest is the same as in Embodiment 1.

[0045] Example 4

[0046] In this embodiment, the amount of Graphene Olefin Particles added is 4 parts, and the rest is the same as in Embodiment 1.

[0047] Example 5

[0048] In this embodiment, the amount of Graphene Olefin particles added is 8 parts, and the rest is the same as in Embodiment 1.

[0049] Example 6

[0050] The addition amount of the composite particles in this embodiment is 0.1 g per 100 g of the masterbatch, and the rest is the same as in Example 1.

[0051] Example 7

[0052] The addition amount of the composite particles in this embodiment is 0.3 g per 100 g of the masterbatch, and the rest is the same as in Embodiment 1.

[0053] Example 8

[0054] The addition amount of the composite particles in this embodiment is 0.8 g per 100 g of the masterbatch, and the rest is the same as in Example 1.

[0055] Example 9

[0056] The addition amount of the composite particles in this embodiment is 1.5 g per 100 g of the masterbatch, and the rest is the same as in Example 1.

[0057] Comparative Example 1

[0058] In this comparative example, no graphyne particles were added, and the rest was the same as in Example 1.

[0059] Comparative Example 2

[0060] In this comparative example, no graphyne particles were added, and the rest was the same as in Example 7.

[0061] Comparative Example 3

[0062] In this comparative example, no graphyne particles are added, and the rest is the same as in Example 8.

[0063] Comparative Example 4

[0064] In this comparative example, no graphyne particles were added, and the rest was the same as in Example 9.

[0065] Comparative Example 5

[0066] In this comparative example, no composite particles are added, and the rest is the same as in Example 1.

[0067] Comparative Example 6

[0068] In this comparative example, no composite particles are added, and the rest is the same as in Example 3.

[0069] Comparative Example 7

[0070] In this comparative example, no composite particles are added, and the rest is the same as in Example 4.

[0071] Comparative Example 8

[0072] In this comparative example, no composite particles are added, and the rest is the same as in Example 5.

[0073] Comparative Example 9

[0074] In this comparative example, no graphyne particles and composite particles are added, and the rest is the same as in Example 1.

[0075] Comparative Example 10

[0076] In this comparative example, no composite particles were added, and 1 part of graphyne particles was replaced by 2 parts of graphene particles (Chengdu Jia Material Technology Co., Ltd., model: JCHGRAP1), and the rest was the same as in Example 1.

[0077] Comparative Example 11

[0078] In this comparative example, 1 part of graphyne particles is replaced by 1 part of graphene particles, and the rest is the same as in Example 1.

[0079] Comparative Example 12

[0080] In this comparative example, 1 part of graphyne particles is replaced by 2 parts of graphene particles, and the rest is the same as in Example 1.

[0081] Comparative Example 13

[0082] In this comparative example, 1 part of graphyne particles is replaced by 4 parts of graphene particles, and the rest is the same as in Example 1.

[0083] Comparative Example 14

[0084] In this comparative example, 1 part of graphyne particles is replaced by 8 parts of graphene particles, and the rest is the same as in Example 1.

[0085] The toners of Examples 1 to 9 and Comparative Examples 1 to 9 were evaluated for compatibility, whether the toner consumption was reduced, whether the transfer rate was improved, and whether the color density was excellent under a high temperature and high humidity environment (HH environment) of 24°C and a humidity of 50%RH by the following method. The charge amount and color density stability under a low temperature and low humidity environment (LL environment) of 10.0°C and a humidity of 20%RH were evaluated. The results are shown in Tables 1 to 5 below. In addition, each evaluation was performed after the following evaluation machine was left to stand for 24 hours in each environment (HH environment or LL environment).

[0086] Evaluation machine:

[0087] A magnetic single-component image forming apparatus (a modified machine of "P2040dn" manufactured by Kyocera Corporation) was used as an evaluation machine. An evaluation object (one of the toners of Examples 2-9 and Comparative Examples 1-3) was placed in the developing device of the evaluation machine. A4-size plain paper (70 g / sheet, manufactured by Kinglight Office Co., Ltd.) was used as a recording medium.

[0088] Development durability test:

[0089] A magnetic single-component image forming device (a modified machine of "P2040dn" manufactured by Kyocera Corporation) was used as an evaluation machine. The durability test was carried out as follows: a solid image was formed on 3000 recording media using the evaluation machine in a high temperature and high humidity environment (32.5°C / 80% RH) and a low temperature and low humidity environment (10°C / 20% RH). The color density (initial color density) of the solid image formed on the first sheet and the color density (color density after endurance printing) of the solid image formed on the 3000th sheet were measured using the above-mentioned reflection densitometer. The absolute value (ΔID) of the difference between the initial color density and the color density after endurance printing was calculated. The initial color density, the color density after endurance printing, and ΔID were evaluated according to the following criteria.

[0090] (Baseline for initial color density and color density after endurance printing) A (good): 1.3 or more and 1.4 or less; B (relatively good): 1.2 or more and less than 1.3; C (poor): less than 1.2 or more than 1.4;

[0091] (Criteria for ΔID) A (good): 0.05 or less; B (relatively good): more than 0.05 and less than 0.1; C (poor): more than 0.1.

[0092] Electrical stability test:

[0093] Using the evaluation machine, a pattern image is formed on 3000 recording media (printing coverage 5%). Using the above-mentioned Q / m meter, the toner is sucked from the toner layer in the area immediately before the developing clamping portion on the developing sleeve of the developing device, and its charge [μC / g] is measured. The obtained value is used as the charge after endurance printing. The initial charge and the charge after endurance printing are evaluated according to the following criteria.

[0094] (Criteria for charge amount under LL environment) A (good): charge amount is 10 μC / g or more and 30 μC / g or less. B (bad): charge amount is less than 10 μC / g or exceeds 30 μC / g.

[0095] Compatibility Test:

[0096] The evaluation machine was used to test under normal temperature and humidity, and was compatible with OEM TK1170, Bachuan UED-01, and Mitsubishi PK2 target powder tests. After printing 500 pieces of target powder on the evaluation machine, Examples 2-9 and Comparative Examples 1-9 were changed to print 3000 pieces, and a pattern image was formed on the recording medium (printing coverage 5%), and the powder consumption, transfer rate, and color density were recorded. Every 500 pieces of the manuscript were observed and evaluated.

[0097] Powder consumption: Average powder consumption when printing 100 sheets of ISO19752 (5%) standard consumable plates.

[0098] A (good): ≤4g / 100 sheets; B (relatively good): 4-4.5g / 100 sheets; C (poor): >4.5g / 100 sheets.

[0099] Transfer rate: transfer rate; (powder consumption - waste powder) / powder consumption * 100%

[0100] A (good): ≥88%; B (relatively good): 80-88%; C (poor): <80%.

[0101] Color density: A (good): 1.3 or more and 1.4 or less; B (relatively good): 1.2 or more and less than 1.3; C (poor): less than 1.2 or more than 1.4.

[0102] Table 1

[0103]

[0104]

[0105] Table 2

[0106]

[0107] Table 3

[0108]

[0109]

[0110] Table 4

[0111]

[0112] Table 5

[0113]

[0114]

[0115] In summary, the invention includes but is not limited to the above embodiments. Any equivalent substitution or partial improvement made under the spirit and principle of the invention shall be deemed to be within the protection scope of the invention.

Claims

1. A toner containing conductive particles, characterized in that: The invention comprises a toner master particle and an external additive; wherein the toner master particle comprises a binding resin and graphyne particles; the external additive comprises a molybdenum disulfide composite particle coated with a conductive polymer; and the external additive is attached to the surface of the toner master particle; The mass fraction of the binding resin in the toner masterbatch is 40% to 95%, the mass of the graphyne particles is 0.05% to 10% of the binding resin, and the mass of the molybdenum disulfide composite particles coated with the conductive polymer is 0.05% to 2% of the toner masterbatch.

2. A toner containing conductive particles as claimed in claim 1, characterized in that: The mass fraction of the binding resin in the toner masterbatch is 55% to 90%, the mass of the graphyne particles is 1% to 5% of the binding resin mass; the mass of the molybdenum disulfide composite particles coated with the conductive polymer is 0.1% to 1% of the toner masterbatch mass.

3. A toner containing conductive particles as claimed in claim 1, characterized in that: The Graphene Oxide Particles have a sheet diameter of 2 to 10 μm, a thickness of 5 to 13 nm, and an electrical conductivity of (0.5 to 4)×10 2 S / m.

4. A toner containing conductive particles as claimed in claim 1, characterized in that: In the molybdenum disulfide composite particles coated with the conductive polymer, the coverage rate of the conductive polymer on the molybdenum disulfide particles is 20% to 70%, the coating thickness is 0.1 to 10 nm, the particle size of the composite particles is 50 to 500 nm, the resistivity is below 40 Ω·cm, and the sphericity coefficient is greater than 0.95; preferably, in the molybdenum disulfide composite particles coated with the conductive polymer, the coverage rate of the conductive polymer on the molybdenum disulfide particles is 30% to 50%, the particle size of the composite particles is 100 to 200 nm, the resistivity is below 10 Ω·cm, and the moisture content is less than 0.5%.

5. A toner containing conductive particles as claimed in claim 1, characterized in that: In the molybdenum disulfide composite particles coated with a conductive polymer, the conductive polymer is one or more of polypyrrole and its derivatives, polyaniline and its derivatives, polythiophene and its derivatives.

6. A toner containing conductive particles as claimed in claim 1, characterized in that: The toner masterbatch further includes a colorant, a charge regulator, and a release agent.

7. A toner containing conductive particles as claimed in claim 1, characterized in that: The external additives also include silicon dioxide and metal oxide particles.

8. A toner containing conductive particles as claimed in claim 1, characterized in that: The binder resin contains more than 85% by mass of thermoplastic resin.

9. A toner containing conductive particles as claimed in claim 1, characterized in that: The colorant includes carbon black or magnetic iron oxide black, the mass of the carbon black is 10% to 15% of the mass of the bonding resin, and the mass of the magnetic iron oxide black is 60% to 150% of the mass of the bonding resin; the mass of the charge regulator is 2% to 10% of the mass of the bonding resin, and the mass of the release agent is 2% to 20% of the mass of the bonding resin.

10. A method for preparing a toner containing conductive particles according to any one of claims 1 to 9, characterized in that: The method steps include: First, the components of the toner masterbatch are mixed, extruded through an extruder, cooled, crushed, and sieved to obtain the toner masterbatch; then, external additives are added, mixed, and sieved to obtain a toner containing conductive particles.